The biology of pulmonary exacerbations in bronchiectasis - Francesco Amati (European Respiratory Review, 2019)
Bronchiectasis is a heterogeneous chronic disease. Heterogeneity characterises bronchiectasis not only in the stable state but also during exacerbations, despite evidence on clinical and biological aspects of bronchiectasis, exacerbations still remain poorly understood. Although the scientific community recognises that bacterial infection is a cornerstone in the development of bronchiectasis, there is a lack of data regarding other trigger factors for exacerbations. In addition, a huge amount of data suggest a primary role of neutrophils in the stable state and exacerbation of bronchiectasis, but the inflammatory reaction involves many other additional pathways. Cole's vicious cycle hypothesis illustrates how airway dysfunction, airway inflammation, infection and structural damage are linked. The introduction of the concept of a “vicious vortex” stresses the complexity of the relationships between the components of the cycle. In this model of disease, exacerbations work as a catalyst, accelerating the progression of disease. The roles of microbiology and inflammation need to be considered as closely linked and will need to be investigated in different ways to collect samples. Clinical and translational research is of paramount importance to achieve a better comprehension of the pathophysiology of bronchiectasis, microbiology and inflammation both in the stable state and during exacerbations.